High-resolution magnetic resonance imaging demonstrates reduced inferior oblique muscle size in isolated inferior oblique palsy - Ela-Dalman, Noa (2008)
PURPOSE: The diagnosis of isolated inferior oblique muscle palsy is controversial for 2 reasons: first, clinical findings seem inconsistent with our current understanding of oculomotor neuro-anatomy and, second, similar findings can occur with other causes. Because denervated extraocular muscles atrophy, we used high-resolution magnetic resonance imaging (MRI) to assess inferior oblique muscle size in patients with clinically suspected inferior oblique muscle palsy. METHODS: A diagnosis of inferior oblique muscle palsy in 6 patients (4 unilateral, 2 bilateral) was made clinically. High-resolution coronal and sagittal orbital MRI were obtained in subjects with clinical inferior oblique muscle palsy and in 30 age-matched control subjects. Cross sections of the inferior oblique, inferior rectus (IR), and medial rectus muscles were determined together because each is innervated by the common inferior division of the oculomotor nerve. No subject had pupillary abnormalities or other extraocular muscle weakness or restriction. RESULTS: Mean cross-sectional area of the affected inferior oblique muscle (n = 8) at the midpoint of the inferior rectus muscle was 10.2 ± 1.05 mm(2), which was significantly smaller than the value of 18.8 ± 3.6 mm(2) for control subjects (n = 58, p < 0.00001). Unilaterally affected inferior oblique muscles were significantly smaller than unaffected inferior oblique muscles (p < 0.05). Mean medial rectus muscle cross section (n = 8) ipsilateral to the affected inferior oblique muscle was 36.8 ± 2.4 mm(2), which was not significantly different from the 35.1 ± 3.7 mm(2) value for the medial rectus muscles of control subjects (n = 61, p > 0.1). Mean inferior rectus muscle cross section (n = 8) ipsilateral to the affected inferior oblique muscle was 32.5 ± 2.3 mm(2), which was significantly greater than the 29.9 ± 3.3 mm(2) measurement for the control subjects (n = 61, p < 0.01). CONCLUSIONS: We used MRI to demonstrate reduced inferior oblique muscle size in patients with clinically diagnosed inferior oblique muscle palsy, supporting the concept of isolated inferior oblique muscle weakness.